Assessing Urban Public Space Quality: A Short Questionnaire Approach - Athina Mela; Evgenia Tousi; George Varelidis (Urban Science)
This study introduces a concise questionnaire designed to evaluate the quality of urban public spaces as a simplified method for collecting community needs and perspectives, enabling these insights to be effectively combined with metrics and viewpoints from policymakers and decision-makers. The case study was carried out in one of the smallest municipalities of Attica, in the town of Kaisariani, Athens, with an emphasis on the central square and the park of the area. Findings show that the majority of respondents prioritize improving the vegetation and lighting of Kaisariani Square, as well as demands for more benches and cultural/art elements. The most important negative experience was the feeling of neglect and lack of cleanliness. Concerns about lighting and lack of care/cleanliness were also key at the park. Addressing current gaps in the public space assessment literature, the study lays the groundwork for future research and supports the creation of easy-to-use quality assessment tools. In contrast to more analytical approaches, the proposed questionnaire tool provides a streamlined and efficient method for capturing users’ perceptions of public spaces. Its design ensures that evaluations are not time-consuming or resource-intensive, allowing citizen feedback to be seamlessly integrated into various public space management processes rather than being limited to exhaustive and costly research efforts. As urban environments continue to expand, the adoption of such techniques will be essential for fostering sustainable and resilient communities that prioritize the well-being of their citizens.